OPTIMALISASI CURUG SAWER DESA NEMBOL SEBAGAI WISATA ALAM EDUKATIF DAN REKREATIF DI KECAMATAN MANDALAWANGI, KABUPATEN PANDEGLANG - Wiguna, Wahyu; Suflani , Suflani (Yayasan Education and Social Center, 2026)
Curug Sawer, also known as Curug Sawer, is one of the natural tourism destinations located in Nembol Village, Mandalawangi Subdistrict, Pandeglang Regency. This tourist attraction offers natural waterfalls, rivers, mountainous scenery, camping areas, and supporting recreational facilities. However, the potential of Curug Sawer has not been optimally managed, especially as an educational-based nature tourism destination. Problems identified include limited community capacity in tourism management, lack of educational tourism concepts, minimal environmental awareness, and underutilized local resources. This community service activity aims to optimize Curug Sawer as an educational and recreational nature tourism destination through community empowerment, environmental education, and tourism management assistance. The methods used include socialization, training, mentoring, and participatory activities involving local communities, youth groups, and tourism awareness groups. The results of this activity show increased community understanding of sustainable tourism, improved environmental awareness, and strengthened local participation in tourism management. This program is expected to support the development of Curug Sawer as a sustainable educational tourism destination and improve community welfare.